Superelliptic UWB antipodal Vivaldi antenna design, simulation, optimization, and prototyping for wireless communication and remote sensing applicaitons - Kazıcı, Simay (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2020)
Bu tez çalışmasında, klasik antipodal ve super-eliptik antipodal Vivaldi antenlerin parametrik tasarımı ve parametrik incelenmesi CST Microwave Studio ile yapılmıştır. Bu çalışma sonucunda yansıma katsayısına en çok etkisi olan parametreler belirlenip söz konusu parametrelerin PSO algoritması uygulanarak optimizasyonu gerçekleştirilmiştir. Optimal parametreler bulunduktan sonra antenler bu parameterler ile diğer anten özelliklerini araştırmak üzere simüle edilerek sonuçlar verilmiştir. Bu süreçte VSWR değerine ek olarak optimal anten konfigürasyonu toplam verim, kazanç, yönlülük, ön-arka kazanç oranı gibi diğer anten özellikleri için simüle edilip sonuçlar verilmiştir. Her iki antenin de üretimi fotokimyasal aşındırma tekniği ile gerçekleştirilmiştir. Prototip antenlerin labaratuarda yansıma katsayısı ve super-eliptik antenin farklı frekans değerleri için radyasyon paternleri MVG StarLab Yakın Alan Tarayıcısı ile ölçülmüştür. Ölçüm sonuçları karşılaştırmalı olarak tezde raporlanmıştır.

In this work, conventional and super-elliptical antipodal Vivaldi antennas are investigated. Comprehensive parametric design and simulations for both configurations are performed in CST microwave studio commercial software. Each parameter of both configurations is investigated thus the impact for the reflection coefficient is defined and results are given in the thesis. After the defining the most impactful parameters, defined parameters are optimized using a PSO algorithm. Optimal results for return loss parameter are given. In addition to the VSWR value, other antenna properties are simulated and investigated in the scope of the thesis. Results of total efficiency, front-to-back ratio, gain, directivity, realized gain values are simulated and reported in the thesis. Both antenna configurations are realized. Fabrication is done using photoetching technique. After the fabrication, antennas are measured using VNA and near field scanner. VNA is used to measure the VSWR. Antenna radiation pattern, and antenna properties are measured using MVG StarLab Near Field Scanner. Finally, all results are reported in the thesis.
Kablosuz haberleşme ve uzaktan algılama uygulamalarıiçin ultra-geniş bantlı süper-eliptik antipodal Vivaldi anten tasarımı, simülasyonu, optimizasyonu ve gerçeklenmesi
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering